Evaluasi Kualitas Layanan Website Pemerintah Kota Batu dengan Metode E-Govqual dan Importance Performance Analysis (IPA) - Abdulloh Hamid Sulaiman; Himawat Aryadita; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The President instruction no. 3 / 2003 about national policy and strategy on the development of information technology services at government (e-Government), pushes local government such as Batu City government to participate in its development by providing services through public relation website. However, there are some deficiency in the website based on user experience. This research discusses user's assessment, particularly local people, on website services by public relation department, Batu City government. The users data is collected by spreading the questioner with e-govqual atributes, while assessment analysis is by importance performance analysis (IPA). The recommendation to repair and /or develop will be given based on Heuristic evaluation. The final result of this research points out that the website service is still not macth the expectation of users. The conformity level analysis shows that the final result is <100% i.e <81.89%, while the gap level analysis (gap) is < 0 (negative) i.e. -0.72. From quadrant analysis, 3 attributes that are main priority of repaired and developed and 6 attributes that become low priority of repaired and developed. The above nine attributes is recommended to be repaired and developed based on Heuristic evaluation.